The Screening of Celiac Serology in Pediatric Patients Diagnosed with Type 1 Diabetes Mellitus - Taşkın, Didem Gülcü; Ata, Aysun (Turkish Journal of Gastroenterology, 2023)
Background: This study aims to detect the rate of celiac antibody test positivity in pediatric patients diagnosed with type 1 diabetes mellitus (T1DM) and determine the characteristics of the patient groups diagnosed with and without celiac disease (CD).Methods: This study was conducted retrospectively in Adana City Training and Research Hospital, Pediatric Endocrinology Outpatient Clinic with the patients diagnosed with T1DM between September 17, 2017, and January 1, 2022. The patients were examined by 3 different groups. Group 1: celiac patient group, group 2: serology false positive group, and group 3: serology negative group.Results: The study included 418 patients, 228 (54.5%) males and 190 (45.5%) females. About 6% of the patients (25 patients) were in the celiac patient group, 12.6% (53 patients) in the serology false positive group, and 81.3% (340 patients) in the serology negative group. The age at diagnosis was 10 (7.2-12.9) years in the celiac patient group and 8.8 (6.2-12.00) years in the serology false positive group (P = .559). Among 53 patients in the serology false positive group, spontaneous normalization was observed in 66% (35 patients), and positivity was continued during the test follow-up period in 34% (18 patients). There was no significant difference in terms of sex (P = .101), and HbA1c values at diagnosis (P = .557). Tissue transglutaminase IgA titer was 20× Upper limit of normal (ULN) in the celiac patient group and 2.52× ULN in the serology false positive group.Conclusion: T1DM and CD are both autoimmune diseases concurrently seen together. CD antibody positivity may be observed at the first presentation of T1DM. While the majority of these antibodies become negative during the follow-up, we wanted to highlight the false positive antibody titers and emphasize that these patients should be followed by endocrinologists and gastroenterologists together.Cite this article as: Gülcü Taşkın D, Ata A. The screening of celiac serology in pediatric patients diagnosed with type 1 diabetes mellitus. Turk J Gastroenterol. 2023;34(3):293-297.